DNA Barcoding em Utricularia (Lentibulariaceae) - Pena, Michelle Mendonça [UNESP] (2015)
The family Lentibulariaceae Rich. is considered the largest group of carnivorous plants among the angiosperms. Utricularia is the richest genus with approximately 250 species. Several studies based on morphological identification have been published for the family Lentibulariaceae, but they are limited regarding some groups of species. Hence, DNA Barcoding may be an important alternative. The present study used DNA sequences of chloroplast intergenic spacers trnS-trnG and trnL-trnF and also the mitochondrial gene coxI in order to test them with the DNA Barcoding approach to intraspecific, interspecific and between sections differentiation in the Utricularia genus. Based on the distance analyses, the average intraspecific distance was 0.004 for both chloroplast markers and 0.006 for the coxI gene, the average interspecific distance was 0.260 to trnS-trnG, 0.190 to trnL-trnF, 0.043 to coxI and the average distance between sections was 0.036, 0.029 and 0.025 to trnS-trnG, trnL-trnF and coxI, respectively. The analysis based on Neighbor-Joining tree indicated that most species were grouped into sections according to the proposed for the phylogeny of the genus, forming monophyletic groups. The efficacy of interspecies discrimination was 82% to trnS-trnG and 61% to trnL-trnF, intraspecific discrimination was 36% to trnS-trnG and 23% to trnL-trnF. The mitochondrial gene coxI showed 24% of inter and intraspecific discrimination, with low resolution of species on trees Neighbor-Joining. These results demonstrate that the chloroplast regions have satisfactory information to separate species in clades that corroborate the phylogeny of the group and therefore trnS-trnG and trnL-trnF can be considered good barcodes for the Utricularia genus